(untitled) (Scientific journal of the Fergana State University, 2026)
Marginalization is the process of exclusion of individuals or groups from the central flow of society, systematically invaluable from resources and opportunities.arginalization is the process of exclusion of individuals or groups from the central flow of society, systematically invaluable from rarginalization is the process of exclusion of individuals or groups from the central flow of society, systematically invaluable from resources and opportunities. This article ).